Intramyocardial angiogenetic stem cells and epicardial erythropoietin save the acute ischemic heart - Christian Klopsch; Anna Skorska; Marion Ludwig; Heiko Lemcke; Gabriela Maass; Ralf Gaebel; Martin Beyer; Cornelia Lux; Anita Toelk; Karina Müller; Christian Maschmeier; Sarah Rohde; et al. (The Company of Biologists, 2018)
Ischemic heart failure is the leading cause of mortality worldwide. An early boost of intracardiac regenerative key mechanisms and angiogenetic niche signaling in cardiac mesenchymal stem cells (MSCs) could improve myocardial infarction (MI) healing. Epicardial erythropoietin (EPO; 300 U kg−1) was compared with intraperitoneal and intramyocardial EPO treatments after acute MI in rats (n=156). Real-time PCR and confocal microscopy revealed that epicardial EPO treatment enhanced levels of intracardiac regenerative key indicators (SDF-1, CXCR4, CD34, Bcl-2, cyclin D1, Cdc2 and MMP2), induced transforming growth factor β (TGF-β)/WNT signaling in intramyocardial MSC niches through the direct activation of AKT and upregulation of upstream signals FOS and Fzd7, and augmented intracardiac mesenchymal proliferation 24 h after MI. Cardiac catheterization and tissue analysis showed superior cardiac functions, beneficial remodeling and increased capillary density 6 weeks after MI. Concomitant fluorescence-activated cell sorting, co-cultures with neonatal cardiomyocytes, angiogenesis assays, ELISA, western blotting and RAMAN spectroscopy demonstrated that EPO could promote cardiomyogenic differentiation that was specific of tissue origin and enhance paracrine angiogenetic activity in cardiac CD45−CD44+DDR2+ MSCs. Epicardial EPO delivery might be the optimal route for efficient upregulation of regenerative key signals after acute MI. Early EPO-mediated stimulation of mesenchymal proliferation, synergistic angiogenesis with cardiac MSCs and direct induction of TGF-β/WNT signaling in intramyocardial cardiac MSCs could initiate an accelerated healing process that enhances cardiac recovery.